2011
DOI: 10.1021/es2030438
|View full text |Cite
|
Sign up to set email alerts
|

Surface Urban Heat Island Across 419 Global Big Cities

Abstract: Urban heat island is among the most evident aspects of human impacts on the earth system. Here we assess the diurnal and seasonal variation of surface urban heat island intensity (SUHII) defined as the surface temperature difference between urban area and suburban area measured from the MODIS. Differences in SUHII are analyzed across 419 global big cities, and we assess several potential biophysical and socio-economic driving factors. Across the big cities, we show that the average annual daytime SUHII (1.5 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
767
14
21

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,036 publications
(873 citation statements)
references
References 40 publications
71
767
14
21
Order By: Relevance
“…For all the cities averaged, the annual SUHII in daytime was higher than in nighttime (1.63 • C vs. 0.88 • C), and the SUHII in summer was higher than in winter (3.07 • C vs. 0.41 • C for daytime and 1.09 • C vs. 0.70 • C for nighttime). These results were similar to previous studies [3,10,32] and can be attributed to vegetation activities. Vegetation can release more latent heat fluxes but less sensible heat fluxes (than the artificial impervious surfaces: roads and buildings) by evapotranspiration and then decrease the temperature [3,26,35].…”
Section: -Year Averaged Ues On Vegetation and Suhiisupporting
confidence: 93%
See 3 more Smart Citations
“…For all the cities averaged, the annual SUHII in daytime was higher than in nighttime (1.63 • C vs. 0.88 • C), and the SUHII in summer was higher than in winter (3.07 • C vs. 0.41 • C for daytime and 1.09 • C vs. 0.70 • C for nighttime). These results were similar to previous studies [3,10,32] and can be attributed to vegetation activities. Vegetation can release more latent heat fluxes but less sensible heat fluxes (than the artificial impervious surfaces: roads and buildings) by evapotranspiration and then decrease the temperature [3,26,35].…”
Section: -Year Averaged Ues On Vegetation and Suhiisupporting
confidence: 93%
“…However, the SNLD data has a blooming effect; the urban area extracted from SNLD was usually larger than the real urban area [44,47]. Figures 2c and 3c showed that the urban areas at WH extracted from SNLD contained the Yangtze River and some lakes, which should be removed in SUHI's study [3,10,48]. In addition, MODIS LCD can extract the water body accurately (Figures 2d and 3d).…”
Section: Extraction Of Urban Areamentioning
confidence: 97%
See 2 more Smart Citations
“…Most metropolitan cities in US and around the world have experienced the massive flooding in severe storm and urban heat island (UHI) effects in hot summer due to the replacement of natural open and vegetated land surfaces with artificial concrete infrastructure and impermeable, dry surfaces [104,105]. Solar energy is converted to more sensible heat, rather than latent heat.…”
Section: Natural/green Infrastructurementioning
confidence: 99%